Valorization of Waste Cooking Oil into Biodiesel via Bacillus stratosphericus Lipase Amine-Functionalized Mesoporous SBA-15 Nanobiocatalyst - Abdallah R. Ismail; Hamdy Kashtoh; Mohamed A. Betiha; Salem A. Abu Amr; Kwang-Hyun Baek; Nour Sh. El-Gendy (International Journal of Chemical Engineering, 2022)
In this study, evaporation-induced self-assembly was applied to prepare amine-functionalized nano-silica (NH2-Pr-SBA-15). That was simply used to immobilize Bacillus stratosphericus PSP8 lipase (E–NH2–Pr-SBA-15), producing a nanobiocatalyst with good stability under vigorous shaking and a maximum lipase activity of 45 ± 2 U/mL. High-resolution X-ray diffractometer, Fourier transform infrared spectroscopy, N2 adsorption-desorption, field-emission scanning electron, and high-resolution transmission electron microscopic analyses proved the successful SBA-15 functionalization and enzyme immobilization. Response surface methodology based on a 1/2 fraction-three-levels face center composite design was applied to optimize the biodiesel transesterification process. This expressed efficient percentage conversion (97.85%) and biodiesel yield (97.01%) under relatively mild operating conditions: 3.12 : 1 methanol to oil ratio, 3.08 wt.% E–NH2–Pr-SBA-15 loading, 48.6°C, 3.19 h at a mixing rate of 495.53 rpm. E–NH2–Pr-SBA-15 proved to have a long lifetime, operational stability, and reusability.